2022
DOI: 10.3389/fphar.2022.1017391
|View full text |Cite
|
Sign up to set email alerts
|

Real-world study of antiresorptive-related osteonecrosis of jaw based on the US food and drug administration adverse event reporting system database

Abstract: Objective: This study aims to explore the risk signals of osteonecrosis of the jaw induced by antiresorptive drugs and provide references for the clinical safety application.Method: According to the FDA’s Adverse Event Reporting System (FAERS), from January 2004 to September 2021, we chose “Osteonecrosis of the jaw (10064658)” and “Exposed bone in jaw (10071014)” as preferred terms, “antiresorptive drugs” as the target drugs, and primary suspect drug as the drug role code in the dataset. We evaluated the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The IL-6 expression was moderate in groups 1 (IRS 4), 2 (6), and 3 (6). In groups 4 and 5, the expression was mild (IRS 2) (Fig.…”
Section: Histological and Immunohistochemical Results Of Medication D...mentioning
confidence: 84%
See 1 more Smart Citation
“…The IL-6 expression was moderate in groups 1 (IRS 4), 2 (6), and 3 (6). In groups 4 and 5, the expression was mild (IRS 2) (Fig.…”
Section: Histological and Immunohistochemical Results Of Medication D...mentioning
confidence: 84%
“…In previous research and meta-analyses, the incidence of BRONJ in patients with multiple myeloma treated with pamidronate and zoledronate was reported, with the risk for developing BRONJ by pamidronate alone ranging from 0 to 18% 8,12 . According to data obtained from the FDA Adverse Event Reporting System (FAERS) from January 2004 to September 2021, cases of pamidronate were mainly reported from Africa (25.58%), followed by South America (6.65%), North America (3.58%), Oceania (2.05%), and Europe (0.51%) 6 . BRONJ pathogenesis is multifactorial, and its exact mechanism is not fully understood 5 .…”
Section: Acknowledgementsmentioning
confidence: 99%
“…There are, however, exceptions to the rule. For example, Hoefert et al reported MRONJ stage III of the maxilla after 3 low doses of DNO at 6-month intervals in a 58 years old female [17]. Tofé et al [21] reported the mean treatment time till MRONJ development with DNO to be 30.8 ± 3.9 months for low doses of DNO.…”
Section: Discussionmentioning
confidence: 99%
“…They found that these risk signals were consistent with the incidence of drug‐induced AEs and encouraged the use of the FAERS database for analysis of drug‐induced AE risks. Similarly, Peng et al 31 developed a study based on the FAERS database, using signal detection methods to mine AE database information. The study aimed to assist in discovering drug safety signals, providing reference for drug risk management and evaluation, and compensating for the limitations of evaluation methods in drug clinical trials.…”
Section: Discussionmentioning
confidence: 99%